2016
DOI: 10.1093/asj/sjw074
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Wrinkles: Facial Aging and Facial Distortion During Sleep

Abstract: Wrinkles are just one indicator of facial aging, but an indicator that is of prime importance in our world of facial aesthetics. Wrinkles occur where fault lines develop in aging skin. Those fault lines may be due to skin distortion resulting from facial expression or may be due to skin distortion from mechanical compression during sleep. Expression wrinkles and sleep wrinkles differ in etiology, location, and anatomical pattern. Compression, shear, and stress forces act on the face in lateral or prone sleep p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(34 citation statements)
references
References 57 publications
0
34
0
Order By: Relevance
“…(v) Ercan et al [3] proposed that there is a correlation between the level of facial asymmetry and facial side. Anson et al [31] explored that facial wrinkles are developed by the compression during sleep which also contribute to facial skin expansion. The experimental results presented in our study support these notions, by showing that bilateral facial asymmetry based asymmetric right face images can be used for age estimation of a given face image with reduced MAE compared to its counterparts i.e., the original and left asymmetric face images.…”
Section: Discussionmentioning
confidence: 99%
“…(v) Ercan et al [3] proposed that there is a correlation between the level of facial asymmetry and facial side. Anson et al [31] explored that facial wrinkles are developed by the compression during sleep which also contribute to facial skin expansion. The experimental results presented in our study support these notions, by showing that bilateral facial asymmetry based asymmetric right face images can be used for age estimation of a given face image with reduced MAE compared to its counterparts i.e., the original and left asymmetric face images.…”
Section: Discussionmentioning
confidence: 99%
“…Exhibit 1: Pierard Classification of Wrinkles [26]  Atrophic wrinkles develop in exposed and nonexposed skin, disappear with skin traction, change in orientation with body posture, and are due to atrophy of the extracellular matrix.  Elastotic wrinkles develop in sun exposed skin, exhibit solar elastosis, become progressively permanent, and do not disappear with perpendicular traction.…”
Section: Factors Involved In Skin Agingmentioning
confidence: 99%
“…Expression wrinkles and sleep wrinkles differ in etiology, location, and anatomical pattern. Compression, shear, and stress forces act on the face in lateral or prone sleep positions ( Figure 6) [26]. [26].…”
Section: C) Lifestyle-related Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually skin wrinkles emerge and increase along with the aging processes, and extensive skin wrinkles exist in elder mammals, especially for facial wrinkles. According to histological differences and possible causes, skin wrinkles were typically classified into five categories: atrophic wrinkles, elastotic wrinkles, expressional wrinkles, gravitational wrinkles and sleep wrinkles, respectively [1–4]. It has been reported that many intrinsic and extrinsic factors contributed to skin wrinkle development and formation [4, 5], which included slower epidermal turnover, increased skin fragility, decreased nutrients transfer between skin layers, loss of sebaceous glands and reduced oil production in skin, loss of fat support and less padding of fat tissue under skin, ultraviolet oxidative damage, harsh weather and pollution, and repeated skin movement.…”
Section: Introductionmentioning
confidence: 99%